2013
DOI: 10.1007/s10059-013-2245-5
|View full text |Cite
|
Sign up to set email alerts
|

ATHB17 Is a Positive Regulator of Abscisic Acid Response during Early Seedling Growth

Abstract: We performed activation tagging screen to isolate abscisic acid (ABA) response mutants. One of the mutants, designated ahs10 (ABA-hypersensitive10), exhibited ABA-hypersensitive phe-notypes. TAIL-PCR analysis of the mutant revealed that T-DNA was inserted in the promoter region of the Arabidopsis gene, At2g01430, which encodes a homeodomain-leucine zipper protein ATHB17. Subsequent expression analysis indicated that ATHB17 was activated in ahs10. To recapitulate the mutant phenotypes, we prepared ATHB17 OX lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 30 publications
5
24
0
Order By: Relevance
“…However, at mature stage, ATHB17 was mainly expressed in roots (Fig. 1A-g), in agreement with the results of Park et al 36…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…However, at mature stage, ATHB17 was mainly expressed in roots (Fig. 1A-g), in agreement with the results of Park et al 36…”
Section: Resultssupporting
confidence: 92%
“…By examining GFP florescence in root of the transgenic plant, we found that ATHB17 was predominantly localized in the nucleus (Fig. 1E), which is consistent with the previous report36.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations